Generative SLA in the age of minimalism features, interfaces, and beyond : selected proceedings of the 15th Generative approaches to second language acquisition conference - Leal, Tania; Shimanskaya, Elena; Isabelli, Casilde A. (Language acquisition & language disorders ;, 2022)
"This volume brings together empirical studies and keynote addresses presented at the 15th Generative Approaches to Second Language Acquisition conference hosted by the University of Nevada, Reno in 2019. The studies selected for the volume reflect how the latest developments in generative syntactic theory and psycholinguistic methodologies have impacted second language acquisition research in the last decade: from the linguistic properties under investigation and L1-L2/Ln language pairings down to the specific research questions in each study. Minimalist view of language architecture is at the center of studies investigating L2 acquisition of raising, scope, definiteness, phonological representations, and interlanguage transfer. The volume also showcases the latest research on interface phenomena, language processing, and working memory. Studies analyze data collected with a variety of L2 populations from adult foreign language learners to adolescent L3 learners to heritage speakers"--